THE IMPORTANCE OF DEVELOPING CREATIVE THINKING SKILLS, TEACHING CREATIVE THINKING AND CREATIVITY IN ELEMENTARY SCHOOL STUDENTS - Ruzimurod o‘g‘li, Xusanov Ravshan; F.U.Olloqulova (Journal of Higher Education and Academic Advancement, 2024)
This article reflects on the identification and development of creative thinking skills in primary school students. Creative thinking has been highlighted for its benefits for the child and its benefits for the educational knee and the development of creativity and creativity.